Carbon footprint assessment among staffs in a higher public institution - Abdullah S.; Halim N.A.; Mansor A.A.; Mohd Napi N.N.L.; Ahmed A.N.; Ismail M. (International Journal of Scientific and Technology Research, 2023)
Higher education institution is often being addressed as sustainability shifting models, which have an important role towards promoting low-carbon lifestyles. This study investigates the lifestyles pertaining to personal carbon emissions of employees of higher education institutions related with households, transport, travel, food, products and services, in order to conceptualize the emission of Greenhouse Gases (GHG) and usually expressed in equivalent tons of carbon dioxide. This study is significance in reducing the employees personal carbon footprints, next reducing the nation average carbon footprint. Survey was conducted via questionnaire in Universiti Malaysia Terengganu (UMT) at 90% confidence level (n=65). Results showed that emissions were increasing with the wage (MYR1500-MYR13001) and decreasing with education level. Finding of this study indicated that half of the respondents exceeded the nation standard average carbon footprint per person (7.7 metric tons per capita) which 26.23 metric tons was recorded to be the highest carbon footprint of UMT staff. In conclusion, employees of higher education institutions need to properly understand their personal carbon emissions along with reduction mechanisms, in order to promote such the sustainability in higher education institutions. 2020 IJSTR.